Financial innovation: the bright and the dark sides - Beck, Thorsten (2018)
Based on data from 32 countries over the period 1996-2010, this paper is the first to assess the relationship between financial innovation, on the one hand, and bank growth and fragility, as well as economic growth, on the other hand. We find that different measures of financial innovation, capturing both a broad concept and specific innovations, are associated with faster bank growth, but also higher bank fragility and worse bank performance during the recent crisis. These effects are stronger in countries with larger securities markets and more restrictive regulatory frameworks. In spite of these seemingly ambiguous findings, our evidence points to a positive net effect of financial innovation on economic growth: financial innovation is associated with higher growth in countries and industries with better growth opportunities.